Works on Paper : 77th exhibition by artists of Chicago and Vicinity. - The Art Institute of Chicago (Chicago : The Art Institute of Chicago, 1978)
Africano, Nicholas ; Agne, Robert ; Allen, Les ; Altman, Edith ; Arajs, Ilze ; Baer, Alan ; Balicek, Gene ; Balodimas, Stanley J. ; Barber, Robert K. Jr. ; Bauer, Marlene ; Berman, Susan ; Blick, Reba ; Blum, Andrea ; Boswell-Mayer, Nancy ; Bouras, Harry ; Bower, David ; Bowman, Eric ; Boyd, Harold ; Bradley, Barbara J. ; Bramson, Phyllis ; Bravos, Karen L. ; Brown, Greg ; Bryar, Shirley S. ; Burch-Brown, Carol ; etc.
Works on Paper : 77th exhibition by artists of Chicago and Vicinity, The Art Institute of Chicago, September 30 to December 3, 1978
boek